2022
DOI: 10.3390/ma15062150
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Long-Term Clinical Outcome of Feldspathic Ceramic Veneers

Abstract: The purpose of this study was to evaluate the clinical outcome of feldspathic ceramic laminate veneers over a 7-year period using minimally invasive techniques, such as vertical preparation (without prosthetic finish line), or no preparation (no-prep). A total of 170 feldspathic ceramic veneers were cemented in the anterior region, including 70 maxillary and 100 mandibular veneers, after special conditioning of the teeth and restorations. The veneers were evaluated using the FDI World Dental Federation criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
0
14
0
5
Order By: Relevance
“…When using a thinner ceramic, the fraction of light that is not reflected penetrates its surface, where it is mostly transmitted, and as the ceramic thickness increases, the translucency decreases [ 25 , 50 ]. Therefore, we used different ceramic thicknesses of 0.5 mm [ 2 , 51 , 52 , 53 ] and 0.8 mm [ 24 , 54 , 55 ]. Composite discs 1 mm in thickness were used as a substrate to standardize the background and create a common clinical situation [ 27 , 47 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…When using a thinner ceramic, the fraction of light that is not reflected penetrates its surface, where it is mostly transmitted, and as the ceramic thickness increases, the translucency decreases [ 25 , 50 ]. Therefore, we used different ceramic thicknesses of 0.5 mm [ 2 , 51 , 52 , 53 ] and 0.8 mm [ 24 , 54 , 55 ]. Composite discs 1 mm in thickness were used as a substrate to standardize the background and create a common clinical situation [ 27 , 47 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by SG Mihali et al, using minimal invasive preparation is essential in adhesive dentistry. The authors observed no failures for veneers with a maximum thickness of 0.5 mm [ 33 ]. Rammersberg et al showed that a minimally invasive 0.5 mm width of the chamfer would result in good stability for posterior metal-free Artglass crowns cemented by adhesive technique [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…En rehabilitación oral se encontraron 479 casos clínicos empleando esta técnica en coronas, carillas y puentes fijos con un periodo de seguimiento de 6 años; llama la atención la denominada "ortodoncia protésica o POA" que permite movimientos dentales; por ejemplo, si se requiere un movimiento mesial del pilar, se desgasta más su lado opuesto distal para que el diente pueda moverse mesialmente. La evidencia científica de este enfoque protésico fue escasa, tan solo 3 casos clínicos ocuparon POA con un seguimiento mínimo de un año (4)(5)8,(12)(13)(14)(15)(16)18,19,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) .…”
Section: Casos Clínicos Reportadosunclassified
“…Al igual que Comlekoglu (45) , quien observa que el BOPT soporta mayor tensión en el margen de las restauraciones a comparación del hombro y chaflán que presentan valores más bajos y, por lo tanto, mayor resistencia. Sin embargo, García et al (19) , demostraron para cementar las prótesis, seguido de la colocación de glicerina para eliminar la capa inhibida de oxígeno y se retira cualquier tipo de excesos (8,9,(11)(12)(13)(14)19,20,28,31,33,35,45) .…”
Section: Cementación Adhesivaunclassified